Hydrophobic membrane development for MD application - Koh, Bao Yun. (2012)
Membrane distillation (MD) has been the emerging feasible technology to meet the increasing demands in portable water. With environmental-friendly and favorable operating procedures compared to other distillation systems, MD is considered to be the alternative approaches for replacing conventional desalination technologies. However, low permeate flux and limited availability of suitable commercial membranes have been the major setbacks in implementing MD process into commercial scale. The membrane characteristics that attribute to the hydrophobicity (in terms of wetting resistance) and permeate flux performances of hollow fiber membranes are the main considerations in the report.